2014
DOI: 10.1021/ef402285n
|View full text |Cite
|
Sign up to set email alerts
|

Control of CO2 Permeability Change in Different Rank Coals during Pressure Depletion: An Experimental Study

Abstract: The gas permeability of different rank coals varies because of the summative effects of increasing effective stress, gas slippage, and coal matrix shrinkage during gas pressure depletion. In this paper, the natures of CO 2 permeability change were primarily investigated in a high-volatile A bituminous coal (core D2-2), a moderate volatile bituminous coal (core S1), and an anthracite coal (core P11-2-1). Under a 4.3 MPa confining stress condition, as the gas pressure declines, the CO 2 permeability of core D2-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 42 publications
0
54
0
Order By: Relevance
“…The effect of effective stress on shale permeability is closely related to shale pore-fracture system (Chalmers et al, 2012). In the study by Li et al (2014), they reported that the coal with a lower permeability will have a stronger sensitivity of the permeability to the effective stress. Zhang et al (2015b) investigated the impacts of nanopore structure and elastic properties on shale permeability, and showed that (a) pore compressibility increased with a decreasing pore aspect ratio and Youngs modulus; (b) the permeability of micro-fractures in shale were more sensitive to effective stress than hydraulic fractures.…”
Section: Effective Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of effective stress on shale permeability is closely related to shale pore-fracture system (Chalmers et al, 2012). In the study by Li et al (2014), they reported that the coal with a lower permeability will have a stronger sensitivity of the permeability to the effective stress. Zhang et al (2015b) investigated the impacts of nanopore structure and elastic properties on shale permeability, and showed that (a) pore compressibility increased with a decreasing pore aspect ratio and Youngs modulus; (b) the permeability of micro-fractures in shale were more sensitive to effective stress than hydraulic fractures.…”
Section: Effective Stressmentioning
confidence: 99%
“…and is mathematically expressed by the Klinkenberg equation. Gas slippage causes that the apparent gas permeability is greater than liquid permeability (Klinkenberg, 1941;Li et al, 2014;Firouzi et al, 2014). The slippage effect is mainly affected by pore size and gas pressure but is not obviously influenced by the temperature (Fig.…”
Section: Gas Slippage and Knudsen Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption of hydrocarbons may affect hydrocarbon migration in the subsurface [1], which significantly impacts the recovery from unconventional reservoirs [2][3][4][5][6]. Clay minerals form the primary adsorbent surface for adsorbed hydrocarbons in mudstone/shale [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Then, experiments are carried out to determine the adsorption capacity of minerals (e.g., clay minerals, quartz, feldspar, calcite and dolomite) as a function of equilibrium time or hydrocarbon concentration under a certain temperature. Previous studies showed the following: (1) for shale-oil, clay minerals had the highest adsorption capacity (18.0 mg/g), quartz had an intermediate value (3.0 mg/g), and carbonates had the lowest adsorption capacity (1.8 mg/g) [39]; (2) for quartz, the adsorbed amount (2 mg/g) of asphaltene [36], which was diluted with a solution of n-heptane and toluene, is apparently lower than that of asphaltene diluted with toluene (4.5 mg/g) [45] and 6.4 mg/g [44]; (3) feldspar has a greater adsorption capacity than quartz [45]; (4) for calcite, the maximum adsorbed amount of polar compounds (resin and asphaltene) is 2.1-3.6 mg/g [42]; and (5) when compared to limestone, dolomite has a smaller adsorption capacity and a smaller adsorbed amount of asphaltene diluted in toluene [46].…”
Section: Introductionmentioning
confidence: 99%